The Impact of Socioeconomic Inequalities on the Risk of Hypertension in Bangladesh: A Systematic Review and Meta‐Analysis - Kabir Hossain; Tonmoy Alam Shuvo; Asma‐Ul Hosna; Dipu Rani Dey (The Journal of Clinical Hypertension)
ABSTRACT Hypertension is a prevalent health issue in Bangladesh, impacting a significant portion of the population. This meta‐analysis explored how social status inequalities impact hypertension risk in Bangladesh. We systematically searched various electronic databases and rigorously selected 12 studies for inclusion in the analyses. The I2 statistic measured between study heterogeneity, and pooled effect estimates were obtained using the DerSimonian and Laird random effects model to address this variability. Publication bias was assessed through a funnel plot and Egger's test. Sensitivity analysis was conducted to evaluate the robustness of the findings. All analyses were performed using STATA 17. The analyses indicated that females had a significantly higher risk of developing hypertension compared to males, with a pooled odds ratio (OR) of 1.15 (95% confidence interval [CI]: 1.02–1.27). Urban residents showed a pooled OR of 1.11 (95% CI: 1.03–1.19) compared to rural residents. The pooled ORs for hypertension were 1.02 (95% CI: 0.89–1.14) for primary education, 1.07 (95% CI: 0.94–1.21) for secondary education, and 1.25 (95% CI: 1.03–1.47) for higher secondary education, suggesting an increasing risk with higher education levels. Wealth status showed a pooled OR of 1.08 (95% CI: 0.87–1.29) for the poorer class, 1.13 (95% CI: 1.04–1.22) for the middle class, 1.38 (95% CI: 0.68–2.07) for the richer class, and 1.49 (95% CI: 0.97–2.00) for the richest class, indicating a greater risk of hypertension among wealthier individuals. Working individuals had a 39% lower risk of hypertension (OR = 0.61, 95% CI: 0.43–0.80) compared to nonworking individuals.